Prototipe Sistem Kontrol dan Monitor Tanaman Hidroponik pada Sayuran Pakcoy Berbasis Internet of Things - Muhammad Fadlil; Firmawati, Nini (Universitas Andalas, 2025)
A prototype of hydroponic plant control and monitoring system for pakcoy vegetables using NodeMCU ESP8266 with notification via Telegram has been produced. This system can facilitate farmers to monitor and control hydroponic plants remotely with parameters of plant height, pH, water level of hydroponic plants. The prototype is designed using 2 HC-SR04 ultrasonic sensors, pH sensors, servo motors, NodeMCU ESP8266, and telegram applications using the Internet of Things (IoT). Tests were carried out by observing pakcoy plants for 28 days after seeding. The measurement results displayed via telegram found that the percentage error of plant height, water pH, and water level are 1.88%, 1.38%, and 6.81%, respectively, and the water tap can function when the water level on the plant is less than 5 cm. Based on the results obtained, this system can work well.